Analysis of The Implementation of Financial Accounting Standards at CV Skuyindo Jaya Group in Malang City - Kristeni Efelina Cahyafebrianti; Ria Mennita (INCOME: Innovation of Economics and Management, 2025)
This study investigates the implementation of accounting practices and their alignment with Indonesia’s Financial Accounting Standards, specifically the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), within CV Skuyindo Jaya Group a creative service based SME located in Malang City. Utilizing a qualitative descriptive method, data were collected through in-depth interviews with the business owner and financial manager, structured around indicators such as accounting knowledge, bookkeeping practices, reporting capabilities, and compliance with financial standards. Observations and internal financial documents were also reviewed to support the analysis. The findings reveal that while the company has adopted digital tools for basic financial transaction recording, it has yet to implement a complete accounting cycle or fully adhere to the SAK EMKM framework. A significant barrier to compliance is the limited understanding of accounting principles and the structure of financial reports, particularly regarding components such as the Notes to the Financial Statements (CaLK). Moreover, the shortage of competent human resources in accounting contributes to substandard reporting practices. This study highlights how internal organizational capacity and managerial orientation influence the extent to which financial standards are adopted, offering valuable insights into the challenges faced by non public entities in complying with national accounting regulations.